2021
DOI: 10.3389/fendo.2021.689079
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Type 2 Diabetes Mellitus Burden Attributable to Particulate Matter Pollution and Its 30-Year Change Patterns: A Systematic Analysis of Data From the Global Burden of Disease Study 2019

Abstract: BackgroundEpidemiological trends of type 2 diabetes mellitus attributable to fine particulate matter (PM2.5) pollution remain unclear. Here, we estimated spatiotemporal trends of type 2 diabetes mellitus burden attributable to PM2.5 pollution, including ambient particulate matter pollution (APMP) and household air pollution (HAP), from 1990–2019.MethodsData were obtained from the Global Burden of Disease Study 2019 and were analyzed by age, sex, year, and location. Joinpoint regression analysis was applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Once H0 was rejected, significance between 1 segment point and n segment points should be assessed. According to a reference to the APC (annual percentage change) [15], time series were built and taken as independent variables, while the ASPRs and the ASDRs were taken as dependent variables. The R software (R core team, version 4.0.2, Vienna, Austria) was used in visualization for indicators and conducted for linear correlations and coefficients of the SDI to the ASPR and the ASDR.…”
Section: Methodsmentioning
confidence: 99%
“…Once H0 was rejected, significance between 1 segment point and n segment points should be assessed. According to a reference to the APC (annual percentage change) [15], time series were built and taken as independent variables, while the ASPRs and the ASDRs were taken as dependent variables. The R software (R core team, version 4.0.2, Vienna, Austria) was used in visualization for indicators and conducted for linear correlations and coefficients of the SDI to the ASPR and the ASDR.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, 19.9% of diabetes-related deaths and 19.6% of the diabetes-related disability-adjusted life-years (DALY) were attributed to particulate air pollution [ 4 ]. Several systematic reviews have concluded that ambient air pollution is associated with diabetes mellitus [ 5 , 6 ], diabetes type 1 [ 7 ] or gestational diabetes mellitus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 460 million people or 6% of world population were affected by DM ( Khan et al, 2020 ). Furthermore, DM was a top ten globally leading causes of death in 2019, and predicted to reach more than 500 million death in the next twenty-five years ( Wu et al, 2021 ). DM can be managed by lifestyle/behavioral change and/or pharmacotherapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%